Production of turmeric oleoresin microcapsules by complex coacervation with gelatin-gum arabic - Zuanon, Larissa Angélica Cirelli [UNESP]; Malacrida, Cassia Roberta [UNESP]; Telis, Vania Regina Nicoletti [UNESP] (Wiley, 2013)
Turmeric oleoresin is a colorant prepared by solvent extraction of turmeric (Curcuma longa L.). Curcumin, the major pigment present in turmeric, has been described as a potent antioxidant, anti-inflammatory and anticarcinogenic agent. Turmeric pigments are lipid soluble and water insoluble and are sensitive to light, heat, oxygen and pH, which can be overcome by microencapsulation of turmeric oleoresin. The aim of this work was to investigate microencapsulation of turmeric oleoresin by complex coacervation using gelatin and gum Arabic as encapsulants and freeze-drying as the drying method. The coacervation process was studied by varying the concentration of biopolymer solution (2.5, 5.0 and 7.5%) and the core material: total encapsulant ratio (25, 50, 75 and 100%). Microcapsules were evaluated for encapsulation efficiency, morphology, solubility and stability to light. Encapsulation efficiency ranged from 49 to 73% and samples produced with 2.5% of wall material and 100% core: encapsulant ratio showed better stability to light. © 2012 Wiley Periodicals, Inc.
Keywords: Anti-inflammatories; Anticarcinogenic agents; Complex coacervation; Drying methods; Encapsulation efficiency; Microcapsules; Potent antioxidants; Wall materials; Adhesives; Coremaking; Microencapsulation; Packaging; Resins; Solvent extraction; Food products; Acacia senegal; Curcuma longa